Architecture and movement : the dynamic experience of buildings and landscapes - Blundell Jones, Peter; Meagher, Mark (2014)
"The experience of movement, of moving through buildings, cities, landscapes and in everyday life, is the only involvement most individuals have with the built environment on a daily basis. Yet this concept of user experience is so often neglected in architectural study and practice. This book tackles this complex subject for the first time, providing the wide range of perspectives needed to tackle this multi-disciplinary topic. Organised in four parts it:documents the architect's, planner's, or designer's approach, looking at how they have sought to deploy buildings as a promenade and how they have thought or written about it. concentrates on the individual's experience, and particularly on the primacy of walking, which engages other senses besides the visual. engages with society and social rituals, and how mutually we define the spaces through which we move, both by laying out routes and boundaries and by celebrating thresholds. analyses how we deal with promenades which are not experienced directly but via other mediums such as computer models, drawings, film and television. The wide selection of contributors include academics and practitioners and discuss cases from across the US, UK, Europe and Asia. By mingling such disparate voices in a carefully curated selection of chapters, the book enlarges the understanding of architects, architectural students, designers and planners, alerting them to the many and complex issues involved in the experience of movement. "--
Moving through Buildings and Landscapes : the Designer's Perspective -- Movement as experienced by the individual.
Includes bibliographical references and index.
Keywords: Space (Architecture) -- Psychological aspects; Landscapes -- Psychological aspects; Walking -- Psychological aspects